Stinging risk and sting pain of the ivy bee, Colletes hederae. Issue 2 (14th March 2020) - Hennessy, Georgia; Balfour, Nicholas J.; Shackleton, Kyle; Goulson, Dave; Ratnieks, Francis L. W.
Abstract : The ivy bee, Colletes hederae, was first detected in Britain in 2001 and is abundant in many locations. Their ground nesting aggregations can occur in public areas and cause concern about stinging risk. Here we assess that risk. The likelihood of being stung or collided with when in an active aggregation was low, with only 1 sting in 10 h of activity (standing, walking, and "gardening") by a human subject. Collisions were low at 6 per hour. The ivy bee sting is frequently unable to penetrate human skin. Only half were able to sting the fingertips and 75% the inner forearm when held against these areas. Pain was scored using a modified Starr/Schmidt scale. Ivy bee stings were significantly less painful than those of honey bee workers Apis mellifera, with similar scores to a nettle sting, Urtica dioica . Pain subsided after 10 min with weals smaller than both honey bees and nettles. The ivy bee venom sac was ca. 39% the volume of that of a worker honey bee. The sting is similar in size to the honey bee sting and barbs were not seen at 35× magnification. We conclude that the ivy bee is not a danger to the public. They rarely sting people active in a nest aggregation area, have a sting that is frequently unable to penetrate human skin and that causes minimal pain for a short duration, comparable to that of a nettle sting. Nettle stings are considered to be annoying but not dangerous.